Decreased by: ___ -
difference: (___ - ___)
27 - (x - 3) is an accurate model of this situation.
7. 3/5 = 4.5/x
3x= 5(4.5)
x = 15/2
8. 6/4 = 9/x
6x= 45
x= 15/2
8. since triangle ABC and ADE are identical,
angle E is also 30 degrees
so angle D = 180-(30+70)=80 degrees
9. 9/3 = x/5
3x = 45
x = 45/3 = 15
Answer:
x = 181 and y = 97
Step-by-step explanation:
let called the first number is x
the second number would be called y
We are given that:
x + y = 278 (1)
x = y + 84 (2)
Let change x in (2) into (1):
y + 84 + y = 278
2y + 84 = 278
Subtract 84 from both side, we got:
2y + 84 - 84 = 278 - 84
2y + 0 = 194
Divide both side by 2, we got:
2y / 2 = 194 / 2
y = 97
Because y = 97 and x + y = 278 so x would equal:
x + 97 = 278
Subtract 97 from both side, we got:
x + 97 - 97 = 278 - 97
x + 0 = 181
x = 181 and y = 97
Hope this helped :3
1.) Solve for x:
5 x + 7 = 3 x + 21
Subtract 3 x from both sides:
(5 x - 3 x) + 7 = (3 x - 3 x) + 21
5 x - 3 x = 2 x:
2 x + 7 = (3 x - 3 x) + 21
3 x - 3 x = 0:
2 x + 7 = 21
Subtract 7 from both sides:
2 x + (7 - 7) = 21 - 7
7 - 7 = 0:
2 x = 21 - 7
21 - 7 = 14:
2 x = 14
Divide both sides of 2 x = 14 by 2:
(2 x)/2 = 14/2
2/2 = 1:
x = 14/2
The gcd of 14 and 2 is 2, so 14/2 = (2×7)/(2×1) = 2/2×7 = 7:
Answer: x = 7
____________________________________________________________
2.) Solve for x:
3 x - 2 (5 - x) = 3 x - 3 (x - 10)
-2 (5 - x) = 2 x - 10:
2 x - 10 + 3 x = 3 x - 3 (x - 10)
Grouping like terms, 3 x + 2 x - 10 = (3 x + 2 x) - 10:
(3 x + 2 x) - 10 = 3 x - 3 (x - 10)
3 x + 2 x = 5 x:
5 x - 10 = 3 x - 3 (x - 10)
-3 (x - 10) = 30 - 3 x:
5 x - 10 = 30 - 3 x + 3 x
3 x - 3 x = 0:
5 x - 10 = 30
Add 10 to both sides:
5 x + (10 - 10) = 10 + 30
10 - 10 = 0:
5 x = 30 + 10
30 + 10 = 40:
5 x = 40
Divide both sides of 5 x = 40 by 5:
(5 x)/5 = 40/5
5/5 = 1:
x = 40/5
The gcd of 40 and 5 is 5, so 40/5 = (5×8)/(5×1) = 5/5×8 = 8:
<span>Answer: x = 8
_________________________________________________________
3.) Solve for x:</span>
5 (x + 1) = 3 (2 x + 3) + 5
3 (2 x + 3) = 6 x + 9:
5 (x + 1) = 6 x + 9 + 5
Grouping like terms, 6 x + 5 + 9 = 6 x + (9 + 5):
5 (x + 1) = 6 x + (9 + 5)
9 + 5 = 14:
5 (x + 1) = 6 x + 14
Expand out terms of the left hand side:
5 x + 5 = 6 x + 14
Subtract 6 x from both sides:
(5 x - 6 x) + 5 = (6 x - 6 x) + 14
5 x - 6 x = -x:
-x + 5 = (6 x - 6 x) + 14
6 x - 6 x = 0:
5 - x = 14
Subtract 5 from both sides:
(5 - 5) - x = 14 - 5
5 - 5 = 0:
-x = 14 - 5
14 - 5 = 9:
-x = 9
Multiply both sides of -x = 9 by -1:
(-x)/(-1) = -9
(-1)/(-1) = 1:
<span>Answer: x = -9</span>
102 and 102
72 and 72
142 and 142